2016
DOI: 10.1534/g3.116.030700
|View full text |Cite
|
Sign up to set email alerts
|

Fruiting Body Formation in Volvariella volvacea Can Occur Independently of Its MAT-A-Controlled Bipolar Mating System, Enabling Homothallic and Heterothallic Life Cycles

Abstract: Volvariella volvacea is an important crop in Southeast Asia, but erratic fruiting presents a serious challenge for its production and breeding. Efforts to explain inconsistent fruiting have been complicated by the multinucleate nature, typical lack of clamp connections, and an incompletely identified sexual reproductive system. In this study, we addressed the life cycle of V. volvacea using whole genome sequencing, cloning of MAT loci, karyotyping of spores, and fruiting assays. Microscopy analysis of spores h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…Upon mating, the two parental sets of HD and PR loci can recombine into four sexually distinct mating types—a system referred to as the tetrapolar mating type system. The origin of the tetrapolar mating type system has been argued to be ancient for basidiomycetes (Burnett 1975; Fraser et al 2007; Hsueh and Heitman 2008; Maia et al 2015), and the genomes of tetrapolar, as well as bipolar and homothallic mushroom-forming species are known to contain both the HD and the PR locus (James et al 2006; Aimi et al 2005; Yi et al 2009; Morin et al 2012; Bao et al 2013; Chen et al 2016). Further developments in mushroom-forming fungi have resulted in often elaborate HD and PR systems that consist of multiple HD and PR subloci, each containing a series of possible alleles (Casselton and Olesnicky 1998; James et al 2004b; Whitehouse 1949; Raper 1966; Casselton 1978; Badrane and May 1999).…”
mentioning
confidence: 99%
“…Upon mating, the two parental sets of HD and PR loci can recombine into four sexually distinct mating types—a system referred to as the tetrapolar mating type system. The origin of the tetrapolar mating type system has been argued to be ancient for basidiomycetes (Burnett 1975; Fraser et al 2007; Hsueh and Heitman 2008; Maia et al 2015), and the genomes of tetrapolar, as well as bipolar and homothallic mushroom-forming species are known to contain both the HD and the PR locus (James et al 2006; Aimi et al 2005; Yi et al 2009; Morin et al 2012; Bao et al 2013; Chen et al 2016). Further developments in mushroom-forming fungi have resulted in often elaborate HD and PR systems that consist of multiple HD and PR subloci, each containing a series of possible alleles (Casselton and Olesnicky 1998; James et al 2004b; Whitehouse 1949; Raper 1966; Casselton 1978; Badrane and May 1999).…”
mentioning
confidence: 99%
“…Bao et al (2013) reported the mating type system of V. volvacea to be similar to the bipolar system in basidiomycetes, suggesting that the organism might be secondarily homothallic. Chen et al (2016a) studied the life cycle of V. volvacea using whole genome sequencing; demonstrating that the heterothallic life cycle is bipolar, as MAT-A, and not MAT-B, controlled heterokaryotization. They cloned the MAT loci and found MAT locus polymorphisms in a series of strains.…”
Section: Pleurotusmentioning
confidence: 99%
“…During the past decade, with the rapid development of high-throughput sequencing technologies, genome-wide expression analysis has been used for investigating genes involved in lignocellulose decomposition, secondary metabolites and fruiting body development in various edible mushrooms, including Schizophyllum commune [7], Ganoderma lucidum [8], Agaricus bisporus [9] and Lentinula edodes [10]. In V. volvacea [3,11,12], the genes responsible for tolerance of low temperature [13,14], the mating-type system and fruit-body development were also explored by comparative transcriptome analysis techniques [15].…”
Section: Introductionmentioning
confidence: 99%